GPR investigations at an Inca-Spanish site in Argentina - Bonomo, Nestor Eduardo (2013)
We present the results of a GPR prospecting carried out at the archaeological site of Batungasta, in the NW region of Argentina. This site was established by the Incas in the 14th century and was later occupied during the Spaniard conquest. Environmental information obtained at this arid zone led us to postulate that parts of the site buildings had been seriously damaged and buried by seasonal flood events as well as aeolian sedimentation. Therefore, we considered applying the GPR method to investigate the existence of buried remains, their architectural characteristics and to provide further evidence about the flows that possibly affected them. This method seemed suitable to attain these goals since it usually provides a good detection capacity for architectural structures and layers in dry environments, as well as good quality maps of the soil. Seven sectors of the site were surveyed using a GPR constant-offset methodology and 500 MHz antennas. The analysis of the data allowed recognizing electromagnetic patterns that could be associated to the existence of walls. In six of the seven sectors, enclosures formed by rock-earth and earth walls were detected and mapped, confirming Incaic-Spanish and Spanish structures, respectively. A sedimentary layer produced by a large flood that covered the structures was detected and mapped, providing evidence of this kind of event and its influence on the site. The maps of this layer were also useful to indirectly visualize the 3D shapes of the discovered walls, which were unclear in many sections of the data and to detect additional anthropogenic structures with very bad preservation conditions. These structures had not been previously identified from analysis of the data sections due to the confusing aspect of the reflections produced at their irregular boundaries